Cultural Differences in Deliberate Counterfeit Purchase Behavior - Sharma, Piyush; Chan, Ricky YK; Davcik, Nebojsa; Ueno, Akiko (Emerald, 2021)
Purpose: This paper explores the moderating effects of four personal cultural orientations or PCOs (independence, interdependence, risk aversion and ambiguity intolerance) on the relationships among counterfeit proneness, subjective norms, ethical judgments, product evaluation and purchase intentions for counterfeit products.